Determinants of early resumption of postpartum sexual intercourse in sub-Saharan Africa: A systematic review and meta-analysis - Habtamu Gebrehana Belay; Enyew Dagnew Yehuala; Simegnew Asmer Getie; Alemu Degu Ayele; Tigist Seid Yimer; Besfat Berihun Erega; Wassie Yazie Ferede; Mulugeta Dile Worke; Gedefaye Nibret Mihretie (Women's Health)
Background: The World Health Organization recommends that all postpartum women be examined for resumed sexual activity. Despite this, postpartum sexual health education and health promotion are not adequately incorporated into current maternal healthcare systems in low- and middle-income nations. There were variations in the prevalence and variables associated with early postpartum sexual intercourse across several studies. Objectives: The purpose of this systematic review and meta-analysis was to evaluate the pooled prevalence and associated factors for early postpartum sexual intercourse in sub-Saharan African countries. Data Sources and Methods: Primary studies were identified using international databases such as Scopus, PubMed, Google Scholar, Embase, and CINAHL. The Newcastle‒Ottawa Scale quality assessment tool was used to evaluate the quality and strength of the included studies. STATA version 17 was used for the meta-analysis. The heterogeneity of the studies and publication bias was examined using I 2 statistics and Egger’s regression test. Subgroup analysis decreased the underlying heterogeneity based on the study years and sample sizes. Results: Seventeen primary articles were included in the meta-analysis with 8507 study participants. The pooled prevalence of early postpartum sexual resumption in sub-Saharan Africa was 39.41% (95% CI: 31.55%–47.27%). Primiparous (OR = 3.32; 95% CI: 2.26–5.90), spontaneous vaginal delivery (OR = 5.98; 95% CI: 1.74–20.51), formula feeding (OR = 2.24; 95% CI: 1.46–3.44), family planning (OR = 2.91; 95% CI: 1.89–4.49), husband pressure (OR = 4.99; 95% CI: 1.38–18.05), have no formal education (OR = 2.36; 95% CI: 1.49–3.76), and monogamy (OR = 4.18; 95% CI: 2.27–7.69) were significantly associated with early postpartum sexual resumption. Conclusion: Four out of 10 women had returned to sexual activity within 6 weeks of giving birth. This suggests that a large proportion of women are more vulnerable to unwanted pregnancies and sexual health problems. Sexual health education and counseling should be incorporated into standard postpartum care to increase contraceptive use and delay unplanned pregnancies.